Chondrogenic Commitment of Human Bone Marrow Mesenchymal Stem Cells in a Perfused Collagen Hydrogel Functionalized with hTGF-β1-Releasing PLGA Microcarrier - Erwin Pavel Lamparelli; Joseph Lovecchio; Maria Camilla Ciardulli; Valentina Giudice; Tina P. Dale; Carmine Selleri; Nicholas Forsyth; Emanuele Giordano; Nicola Maffulli; Giovanna Della Porta (MDPI AG, 2021)
Tissue engineering strategies can be relevant for cartilage repair and regeneration. A collagen matrix was functionalized with the addition of poly-lactic-co-glycolic acid microcarriers (PLGA-MCs) carrying a human Transforming Growth Factor β1 (hTFG-β1) payload, to provide a 3D biomimetic environment with the capacity to direct stem cell commitment towards a chondrogenic phenotype. PLGA-MCs (mean size 3 ± 0.9 μm) were prepared via supercritical emulsion extraction technology and tailored to sustain delivery of payload into the collagen hydrogel for 21 days. PLGA-MCs were coseeded with human Bone Marrow Mesenchymal Stem Cells (hBM-MSCs) in the collagen matrix. Chondrogenic induction was suggested when dynamic perfusion was applied as indicated by transcriptional upregulation of COL2A1 gene (5-fold; p < 0.01) and downregulation of COL1A1 (0.07-fold; p < 0.05) and COL3A1 (0.11-fold; p < 0.05) genes, at day 16, as monitored by qRT-PCR. Histological and quantitative-immunofluorescence (qIF) analysis confirmed cell activity by remodeling the synthetic extracellular matrix when cultured in perfused conditions. Static constructs lacked evidence of chondrogenic specific gene overexpression, which was probably due to a reduced mass exchange, as determined by 3D system Finite Element Modelling (FEM) analysis. Proinflammatory (IL-6, TNF, IL-12A, IL-1β) and anti-inflammatory (IL-10, TGF-β1) cytokine gene expression by hBM-MSC was observed only in dynamic culture (TNF and IL-1β 10-fold, p < 0.001; TGF-β1 4-fold, p < 0.01 at Day 16) confirming the cells' immunomodulatory activity mainly in relation to their commitment and not due to the synthetic environment. This study supports the use of 3D hydrogel scaffolds, equipped for growth factor controlled delivery, as tissue engineered models for the study of in vitro chondrogenic differentiation and opens clinical perspectives for injectable collagen-based advanced therapy systems.